2004
DOI: 10.1111/j.1075-122x.2004.21290.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte Count and Survival Time in Women with Metastatic Breast Cancer

Abstract: While prognostic factors in early stage breast cancer are well documented, few studies have examined predictors of the rate of metastatic progression. The purpose of this study was to examine cytotoxic T-cell lymphocyte (CTL) count as a marker of disease status in women with metastatic breast cancer. This study examined CTL subset counts as predictors of subsequent survival in 113 women with metastatic or recurrent breast cancer. Samples were measured by flow cytometry using monoclonal antibodies for cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…In patients with advanced stage cancer, decreased numbers of CTLs do not inhibit the spread of tumor cells (Liang et al, 1993). This is consistent with the lower percentages of CTLs in metastatic cancer patients compared to non metastatic cancer patients (Blake-Mortimer et al, 2004).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…In patients with advanced stage cancer, decreased numbers of CTLs do not inhibit the spread of tumor cells (Liang et al, 1993). This is consistent with the lower percentages of CTLs in metastatic cancer patients compared to non metastatic cancer patients (Blake-Mortimer et al, 2004).…”
Section: Introductionsupporting
confidence: 87%
“…Also, a significant reduction in the percentages of peripheral CTLs has been found in breast cancer patients with metastases compared to those without metastases (Liang et al, 1993;Alkhateeb et al, 2013). Consistent with these findings, a progressive decrease in both CD4 and CD8 cells has been associated with the spread of disease in patients with breast, malignant melanoma, lung, and colorectal cancers (Blake-Mortimer et al, 2004). Melichar et al found that CD8+CD28+ T cell counts were significantly lower in breast cancer patients then controls but CD8+CD28+ T cell levels increased following doxorubucin-paclitaxel chemotherapy.…”
Section: Survival and Prognostic Factors For First Line Chemotherapymentioning
confidence: 70%
See 1 more Smart Citation
“…Recent data demonstrate that a low number of lymphocytes in a colorectal tumor is associated with poor prognosis. The prognostic value of NLR was investigated in patients diagnosed with colorectal, ovary, and lung cancer and those who underwent liver transplantation, and a strong correlation was found with overall survival (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that worldwide over 50, 8000 women died in 2011 due to breast cancer. 3 Breast cancer is the leading cause of cancer death among females accounting for 23% (1.38 million) of the total cancer cases and 14% (458,400) of the cancer deaths in women. 4,5 Breast cancer is a major public health problem especially in Sub-Saharan Africa, Nigeria inclusive.…”
Section: Introductionmentioning
confidence: 99%